Vocabulary Learning Strategies - Dewi, Ulpa; Siregar, Fitri Rayani; Vinde Rambe, Shokira Linda (English Education : English Journal for Teaching and Learning, 2024)
This study analyzed vocabulary learning strategies used by XI grade students at State Madrasah Aliyah 2 Padang Lawas, focusing on their English language difficulties and lack of interest. A descriptive quantitative research was conducted with 155 students and 61 students as sample. The questionnaire, consisting of 32 items, revealed that cognitive strategies were the most commonly used, followed by determination, memory, social, and metacognitive strategies. The study highlights the challenges students face in learning English.